2003
DOI: 10.1002/cfg.347
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling on global cDNA arrays gives hints concerning potential signal transduction pathways involved in cardiac fibrosis of renal failure

Abstract: Cardiac remodelling with interstitial fibrosis in renal failure, which so far is only poorly understood on the molecular level, was investigated in the rat model by a global gene expression profiling analysis. Sprague-Dawley rats were subjected to subtotal nephrectomy (SNX) or sham operation (sham) and followed for 2 and 12 weeks, respectively. Heart-specific gene expression profiling, with RZPD Rat Unigene-1 cDNA arrays containing about 27 000 gene and EST sequences revealed substantial changes in gene expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…More generally, PCPE-1 has also been used to assess myocardial ECM remodelling, most of the time together with collagens I and III and with the cross-linking enzyme lysyl oxidase, and its up-regulation was for example demonstrated when MI in sedentary rats was compared to MI in exercised rats [108] , after subtotal nephrectomy in rats [117] or after ischemia–reperfusion injury in mice [118] and pigs [119] . All these results demonstrate that PCPE-1 overexpression broadly overlaps collagen overexpression and suggest a central role of PCPE-1 in both replacement and interstitial fibrosis of the heart.…”
Section: Involvement Of Pcpe-1 In Tissue Repair and Fibrosismentioning
confidence: 99%
“…More generally, PCPE-1 has also been used to assess myocardial ECM remodelling, most of the time together with collagens I and III and with the cross-linking enzyme lysyl oxidase, and its up-regulation was for example demonstrated when MI in sedentary rats was compared to MI in exercised rats [108] , after subtotal nephrectomy in rats [117] or after ischemia–reperfusion injury in mice [118] and pigs [119] . All these results demonstrate that PCPE-1 overexpression broadly overlaps collagen overexpression and suggest a central role of PCPE-1 in both replacement and interstitial fibrosis of the heart.…”
Section: Involvement Of Pcpe-1 In Tissue Repair and Fibrosismentioning
confidence: 99%
“…Amann et al have previously presented gene chip array data, pointing to cardiac hypertrophy after STN as early as two weeks post surgery [22]. They have shown that genes encoding for collagens and proteoglycans are upregulated two weeks post surgery, and that 10 weeks later (12 weeks post surgery), a striking upregulation in laminins and integrins is noted.…”
Section: Gene Ontology Gene Function Gene Symbols (Fold-change and P-mentioning
confidence: 99%